2016 24th Mediterranean Conference on Control and Automation (MED) 2016
DOI: 10.1109/med.2016.7535905
|View full text |Cite
|
Sign up to set email alerts
|

A supervisory approach to microgrid demand response and climate control

Abstract: Abstract-Microgrids equipped with small-scale renewableenergy generation systems and energy storage units offer challenging opportunity from a control point of view. In fact, in order to improve resilience and enable islanded mode, microgrid energy management systems must dynamically manage controllable loads by considering not only matching energy generation and consumption, but also thermal comfort of the occupants. Thermal comfort, which is often neglected or oversimplified, plays a major role in dynamic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…behavior. They developed (D. Korkas, 2016) the EMS for joint demand response management and thermal comfort optimization in microgrids equipped with renewable energy sources and energy storage 5 units. They found that the energy costs are reduced and at the same time thermal comfort of the occupants is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…behavior. They developed (D. Korkas, 2016) the EMS for joint demand response management and thermal comfort optimization in microgrids equipped with renewable energy sources and energy storage 5 units. They found that the energy costs are reduced and at the same time thermal comfort of the occupants is maintained.…”
Section: Introductionmentioning
confidence: 99%